Will changes in primary care improve health outcomes? Modelling the impact of financial incentives introduced to improve quality of care in the UK. Issue 3 (2nd June 2004) - McElduff, P; Lyratzopoulos, G; Edwards, R; Heller, R F; Shekelle, P; Roland, M
Abstract : Objectives: To estimate the total health gain from improving the quality of care among patients with cardiovascular disease in line with the quality indicator targets in the new contract for general practitioners (GPs) in the UK. Design: Statistical modelling, applying population impact measures to estimate cardiovascular health gains from achieving treatment targets in the GP contract, taking into account current levels of treatment and control. Main outcome measures: Number of events prevented in the population over 5 years applied to a notional general practice population of 10 000. Results: The greatest health gain in those aged 45–84 years would come from reaching cholesterol reduction targets. This could prevent 15 events in people with coronary heart disease, seven events in those with a history of stroke, and seven events in those with diabetes. Achieving blood pressure control targets in hypertensive patients without the above conditions could prevent 15 cardiovascular events, with further benefits from reducing blood pressure in patients with high blood pressure and coronary heart disease, stroke, or diabetes. Achieving other targets would have smaller impacts because high levels of care are already being achieved or because of the low prevalence of conditions or associated event risk. Conclusion: It is possible to quantify the health gain to a practice population of achieving quality targets such as those set in the new GP contract. The amount of health gain is sensitive to current quality of care, prevalence of conditions, and risk factors, and to the size of change anticipated. Nevertheless, it appears that significant health gains could result from achieving the proposed quality targets.